Reprezentáció és propaganda: I. Erzsébet két oxfordi látogatása - Stróbl, Erzsébet (Per Aspera ad Astra, 2019)
The paper explores the concept of female sovereignty by comparing the two visits of Queen Elizabeth I to the university town of Oxford: first in 1566 and the second in 1592. The analysis of the extant documents shows that the late reign of the Queen became more autocratic and tolerated less discussion on issues of authority. The receptions staged by the scholars included academic disputations that directly addressed general questions of princely power and the Church of England, such as the superiority of law over the king, or the right to dissemble about religious beliefs. Although both visits focused on theoretical issues, the themes of the second were markedly less daring. The paper also examines the rhetoric of Queen Elizabeth’s response to such challenges, and investigates the political and religious contexts of her visits in order to highlight how the Queen’s position as female monarch changed in the last decades of the sixteenth century. Fotó: Bodleian Library, Oxford